2015
DOI: 10.1002/jmor.20415
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of large corneous beta-proteins in the green anole lizard (Anolis carolinensis) suggests that they form filaments that associate to the smaller beta-proteins in the beta-layer of the epidermis

Abstract: The distribution of large corneous beta-proteins of 18-43 kDa (Ac37, 39, and 40) in the epidermis of the lizard Anolis carolinensis is unknown. This study analyses the localization of these beta-proteins in different body scales during regeneration. Western blot analysis indicates most protein bands at 40-50 kDa suggesting they mix with alpha-keratin of intermediate filament keratin proteins. Ac37 is present in mature alpha-layers of most scales and in beta-cells of the outer scale surface in some scales but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Previous immunolabeling studies in the green anole lizard have suggested expression of Beta1, also referred to as Li-Ac40, in the beta-layer of scales on different body sites investigated56. The immunolabeling for this large beta-protein was associated with filaments of 3 nm thickness, i.e.…”
Section: Discussionmentioning
confidence: 77%
“…Previous immunolabeling studies in the green anole lizard have suggested expression of Beta1, also referred to as Li-Ac40, in the beta-layer of scales on different body sites investigated56. The immunolabeling for this large beta-protein was associated with filaments of 3 nm thickness, i.e.…”
Section: Discussionmentioning
confidence: 77%
“…Alternatively, these voids may represent amorphous corneous material, containing glycine-rich beta-keratins, in a poorly stainable, electron-pale matrix ( [10] and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that voids may represent structural remnants of original lipid droplets in developing claw sheath tissue [35,36]. Alternatively, these voids may represent amorphous corneous material in a poorly stainable, electron-lucent matrix ( [10] and references therein). (Online version in colour.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beta proteins Ac37, Ac39 and Ac40 found in mature alpha layer, beta layer of tail, and mature layer of most scales and dewlap, respectively. Beta proteins together with alpha keratins form the denser areas of mature beta layer [36]. However, regenerated scales lose the ability of physiological color change due to the lack of melanophores, precisely iridophores [37].…”
Section: Mechanism Of Tail Regeneration In Anolis Carolinensismentioning
confidence: 99%